Dampak Sosial Media Bagi Kehidupan Anak Masa Kini - Sabrillah, Sitti Nur Aysah; Didipu, Renawati; Rabiah, Rabiah; Aviva, Restu; Friday, Sintya; Faisal, Moh. (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2023)
The impact of gadgets in the era of globalization has positive and negative impacts. Ease of finding information, knowledge, being able to obtain or communicate with each other remotely is one of the positive paths. The existence of children's behavior that lacks socialization, does not understand politeness as result of never socializing is negative impact that many complain about social development in children. The method used in carrying out health education activities is by holding offline counseling at SD Al ALKHAIRAAT 2 PALU, Central Sulawesi. The counseling is carried out using the presentation and answer method. Analysis of article data used was obtained from internet using official website which discussed the topic of Impact of Social Media on the Lives of Today's Children, then analysis method was carried out by selecting articles according to the inclusion criteria and analyzing the content and findings in the articles obtained in study. Based on the results of statistical tests that have been carried out, it shows an increase in children's knowledge before and after being given counseling about the impact of social media on children offline. It can be interpreted that the children of SD AL KHAIRAAT 2 PALU Central Sulawesi already have good knowledge about the Impact of Social Media on the Lives of Today's Children and expected to be able to apply and disseminate the information obtained to friends and family at home. More than half of children have low knowledge about impact of social media. Basically, social media users are not limited by age and time. Everyone, both children, teenagers and adults can have their own social media accounts, especially children.